The effect of silane coupling agent addition on the hardness of non-dental e-glass fiber reinforced composite in removable partial dentures: Study experimental - Safitri, Subiana Hidayatul; Sari, Widya Puspita; Desnita, Eka (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2024)
ABSTRACT Introduction: The use of E-Glass Fiber Reinforced Composite (FRC) in fixed dental prostheses has gained popularity due to its desirable mechanical properties. Achievement optimal hardness is crucial for the long-term success of these prostheses. This study aimed to analyze the effect of the addition of a silane coupling agent on the non-dental E-Glass FRC's hardness in fixed dental prostheses. Methods: This study is a laboratorium eksperimental with a quantitative research approach to investigate the impact of silane coupling agents on the hardness of non-dental E-Glass FRC. Specimens were prepared with varying concentrations of silane coupling agent, and the hardness was measured using standardized testing methods. The laboratory conditions were set up aimed to simulate the conditions encountered in fixed dental prostheses. Results: A significant correlation was revealed between the addition of silane coupling agent and the hardness of non-dental E-Glass FRC. Higher concentrations of silane coupling agent were associated with increased hardness values. The findings provide valuable insights into optimizing the composition of E-Glass fiber non dental FRC for enhanced mechanical properties in fixed dental prostheses. Conclusion: The addition of a silane coupling agent positively influences the hardness of non-dental E-Glass FRC used in fixed dental prostheses. This study contributes to the ongoing efforts to enhance the mechanical performance of dental materials, emphasizing the importance of optimizing silane coupling agent concentrations for improved hardness.KEY WORDS: e-glass, fiber, reinforced, composite, silane coupling agent..Pengaruh penambahan silane coupling agent terhadap kekerasan e-glass fiber non dental reinforced composite pada gigi tiruan cekat: studi eksperimentalABSTRAKPendahuluan: Penggunaan E-Glass Fiber Reinforced Composite (FRC) dalam prostesis gigi cekat semakin populer karena mendukung sifat mekanik yang diinginkan. Pencapaian kekerasan optimal sangat penting untuk keberhasilan jangka panjang prostesis ini. Tujuan penelitian ini adalah menganalisis pengaruh penambahan silane coupling agent terhadap kekerasan FRC E-Glass non-dental pada gigi tiruan cekat. Metode: Jenis penelitian adalah studi eksperimen laboratorium dengan pendekatan penelitian kuantitatif digunakan untuk menyelidiki dampak agen penggandeng silane terhadap kekerasan FRC E-Glass non-dental. Sampel dipersiapkan dengan konsentrasi berbeda dari silane coupling agent, dan kekerasan diukur menggunakan metode pengujian standar. Kondisi laboratorium diatur untuk mensimulasikan kondisi yang dihadapi dalam prostesis gigi cekat. Hasil: Terdapat korelasi signifikan antara penambahan silane coupling agent dan kekerasan FRC E-Glass non-dental. Konsentrasi silane coupling agent yang lebih tinggi terkait dengan peningkatan nilai kekerasan. Temuan ini memberikan wawasan berharga dalam mengoptimalkan komposisi FRC E-Glass fiber non dental untuk meningkatkan sifat mekanik pada prostesis gigi cekat. Simpulan: Penambahan silane coupling agent secara positif memengaruhi kekerasan FRC E-Glass non-dental yang digunakan dalam prostesis gigi cekat. Studi ini memberikan kontribusi pada upaya terus-menerus untuk meningkatkan kinerja mekanik material kedokteran gigi, dengan menekankan pentingnya mengoptimalkan konsentrasi silane coupling agent untuk kekerasan yang lebih baik.KATA KUNCI: e-glass, fiber, reinforced, composite, silane coupling agent